Radionuclide concentrations in soil and lifetime cancer risk due to gamma radioactivity in Kirklareli, Turkey - TOPUZOĞLU, AHMET; KARAVUŞ, MELDA; AY, NADİYE PINAR; HIDIROĞLU, SEYHAN (ELSEVIER SCI LTD, 2009)
The objective of this study is to ovaluate and map soil radionuclides' activity concentrations and environmental outdoor gamma dose rates (terrestrial and cosmic) in Kirklareli, Turkey. The excess lifetime cancer risks are also calculated. Outdoor gamma dose rates were determined in 230 sampling stations and soil samples were taken from 177 locations. The coordinates of the readings were determined by the Global Positioning System (GPS). The outdoor gamma dose rates were determined by Eberline smart portable device (ESP-2) and measurements were taken in air for two minutes at I m from the ground, The average outdoor gamma close rate was 118 +/- 34 nGy h(-1). Annual effective gamma dose of Kirklareli was 144 mu Sv and the excess lifetime cancer risk of 5.0 x 10(-4). Soil samples were analyzed by gamma spectroscopy. The average Ra-226, U-238, Th-232, Cs-137, and K-40 activities were 37 +/- 18 Bq kg(-1), 28 +/- 13 Bq kg(-1), 40 +/- 18 Bq kg-1, 8 5 Bq kg(-1) and 667 +/- 281 Bq kg(-1), respectively. The average soil radionuclides' concentrations of Kirklareli were within the worldwide range although some extreme values had been determined. Annual effective gamma doses and the excess lifetime risks of cancer were higher than the world's average. (c) 2009 Elsevier Ltd. All rights reserved.
Keywords: Soil; Gamma dose; Radioactivity; Lifetime cancer risk; Global Positioning System; Turkey; DOSE ASSESSMENT; SAMPLES; REGION; RATES